The consistency of Islamic and medical perspectives in the control of the COVID-19 pandemic - Mohamed, Mossad Abdelhak Shaban; Van Rostenberghe, Hans; Ramli, Noraida; Ibrahim, Roshidah; Mosaad, Manar; Hasan, Taufiq Hidayat (USIM Press, 2021)
Controlling the current COVID-19 pandemic requires infection control at both the individual and global levels. There is insufficient information on the consistency between Islamic principles and medical guidelines regarding infection control measures. Therefore, this study aimed to explore the consistency between Islamic principles and evidence-based medical recommendations during the pandemic time. A comparison was made between the latest medical infection control recommendations and Islamic references (the Quran and its interpretation, and Sunnah and its explanation). Relevant materials such as books and research articles in Arabic or English were reviewed. The information was then classified into different levels of infection control strategies, which were individual, household, community and healthcare unit levels. This study demonstrated that both Islamic principles and medical guidelines are consistent in terms of infection control, which involves crisis supervision by the infection control authority and specialised agencies, hand and general hygiene, personal protection, seeking specialist consultation and treatment, comprehensive care, guidelines in the event of limited resources, home isolation, travel bans and quarantine. Moreover, it was observed that Islamic principles combine and optimise both the individual frame and societal cohesion.